A parábola da universidade: da disciplina da obediência à codificação da liberdade - Gianfranco Petronio; Maria Luísa Bissoto (Centro Universitário Salesiano de São Paulo, 2015)
In the analysis of the transformative parable that has concerned the university, from the medieval foundation until now, and focused on the central events that have most determined them, i.e., the cultural and social-political changes that started with the rise of modernity (XVI century), have emerged with the spread of the Enlightenment and were finally materialized with the French Revolution, and have deeply and radically changed the paradigms of power. This "revolution" could not invest recipients, purposes and values of higher education, causing an integral and substantial reform, on which we highlight some unexpected and paradoxical results that today are probably the base of some important critical issues directed to the modern university